Detection of high frequency intensity oscillations at RESEDA using the CASCADE detector - Häußler, Wolfgang; Böni, P.; Klein, Martin; Schmidt, C. J.; Schmidt, Ulrich; Groitl, F.; Kindervater, J. (Review of scientific instruments, 2011)
We have explored the technological potential of combining neutron resonance spin echo (NRSE) with the time-of-flight method in quasielastic neutron scattering (QENS) experiments. For these test measurements at the new NRSE instrument RESEDA (FRM II, Munich), we have employed CASCADE, one of the fastest neutron detectors in the world, developed at the University of Heidelberg. Conventionally, scintillation detectors are used, in order to detect neutron intensities with high time resolution. In contrast, we used the new CASCADE detector converting neutrons in thin 10B layers being capable of resolving neutron intensity modulations up to the megahertz regime. This fast detector allows us to abandon the last resonance flip coil of a standard NRSE setup. The classical spin echo signal is replaced by a time-modulated signal. In this setup, fast intensity modulations are present at the detector position. In order to demonstrate, that NRSE-CASCADE operates well up to detector frequencies of 10 MHz, we performed elastic polarization test measurements on a standard sample. The CASCADE detector is a multidetector accumulating counts in 128 × 128 pixels on a surface of 200 mm × 200 mm. We have analyzed the signal in 600 pixels, providing information about the spin phase reaching the detector and about the resolution function of this new variant tested at RESEDA.
Gesehen am 23.09.2022